(untitled) (Central Asian Journal of Medical Sciences, 2022)
Objective: Evaluate the outcome of endoscopic sinus surgery among chronic rhinosinusitis (CRS) patients and assess the quality of life. Methods: 200 CRS patients aged between 17 to 73 who were operated endoscopic sinus surgery at the Otorhinolaryngology department of First Central Hospital between November 2019 and November 2020, were involved in this study. Subjects were divided into 2 groups: 1) CRS with nasal polyp; 2) CRS without nasal polyp. CT changes were evaluated according to Lund-Mackay, Hoover score, and Hounsfield unit before and after surgery. Results: Of the total subjects analyzed, 56 % were male and 44 % were female. The average age of subjects was 38.4 ± 13.9. The tissue radiodensity of the maxillary sinus decreased in both groups significantly. The mean value of 21.3 ± 6.9 HU preoperatively dropped to 13.5 ± 3.9 HU postoperative in the CRSsNP group, while the CRSwNP group had similar results. The preoperative mean value of 20.3 ± 3.9 HU declined to 12.0 ± 2.2 HU after the procedure. For assessment of paranasal sinus mucosal thickness, the mean value of preoperative imaging study in the CRSsNP group measured as 5.5 ± 1.7mm, and then it reduced by 3.8mm to reach 1.7 ± 1.4 mm after the surgery (p < 0.000). Consequently, the CRSwNP group shows similar outcomes such as the preoperative mean value assessed with a thickness of 5.8 ± 1.4 mm, declined by 4.4 mm and reached an almost normal mucosal thickness of 1.5 ± 1.0 mm after the procedure (p < 0.000). Conclusion: ESS for CRS is effective according to the evaluation of the Lund-Mackay, Hoover, and Hounsfield unit, and it was statistically significant (p < 0.000).